Analysis of Tax Awareness By Modernizing the Taxation System With Compliance Paying Taxes During a Pandemic: Analisis Kesadaran Pajak Dengan Modernisasi Sistem Perpajakan Dengan Kepatuhan Membayar Pajak Di Masa Pandemi - Esty Safira Hediati; Santi Rahma Dewi (Academia Open, 2021)
Taxes are one of the major sources of revenue for the State and also an important source of funds for national financing. This study aims to describe and analyze taxpayer awareness of tax compliance. And To describe and analyze the modernization of the taxation system for tax compliance. This research uses qualitative research. The object of research is PT Sadana Combinatama Sidoarjo Expedition Service, the type of data is qualitative data, data sources are obtained from interviews, observations and documentation, data analysis using Miles and Hubermen theory includes data reduction, data presentation, and verification. The results of this study PT. Sadana Sidoarjo Branch has a good awareness of obligations as corporate taxpayers, by having a TIN, business license and carrying out tax obligations in accordance with applicable regulations and Modernization of the new tax system can be carried out by companies using eSPT. This is also intended so that tax payments and reporting can be carried out. practically and efficiently paying tax compliance